2013
DOI: 10.1007/978-1-62703-475-3_2
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles: Toxicity, Radicals, Electron Transfer, and Antioxidants

Abstract: In recent years, nanoparticles have received increasing attention in research and technology, including a variety of practical applications. The bioactivity appears to be related to the small particle size, in addition to inherent chemical activity as electron transfer (ET) agents, generators of reactive oxygen species (ROS) with subsequent oxidative stress (OS), and as antioxidants (AOs). The mechanism of toxicity, therapeutic action, and AO property is addressed based on the ET-ROS-OS approach. There are sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 131 publications
0
20
0
Order By: Relevance
“…11,37,38 This was consistent with a previous report demonstrating the effects of surface modification on AuNCs' in vivo pharmacokinetics. [43][44][45] In contrast to the large AuNPs, AuNCs have less concern mainly due to the lower MPS accumulation. This differed from the large AuNPs in various shapes which showed constant hepatic/splenic retentions.…”
Section: Resultsmentioning
confidence: 99%
“…11,37,38 This was consistent with a previous report demonstrating the effects of surface modification on AuNCs' in vivo pharmacokinetics. [43][44][45] In contrast to the large AuNPs, AuNCs have less concern mainly due to the lower MPS accumulation. This differed from the large AuNPs in various shapes which showed constant hepatic/splenic retentions.…”
Section: Resultsmentioning
confidence: 99%
“…It has been well demonstrated that nanoparticle exposure induces the production of ROS (Nel A, 2006, Roy et al, 2014, Kovacic P, 2013, Apopa PL, 2009). The increase in the production of ROS within a cell can lead to damage of DNA, proteins or lipids (Watson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This antioxidant activity could be linked to the transfer of free electrons from the oxygen atom of nanoparticles to free radicals present at the nitrogen atom of DPPH molecules. It has been reported that many of the metal nanoparticles can scavenge free radicals and act as antioxidants [49]. Moreover, a study by [36] reported that the antioxidant activity is mainly due to high surface to volume ratio of the nanostructures.…”
Section: Antioxidant Activitymentioning
confidence: 99%